2019
DOI: 10.3389/fphar.2019.01274
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Dimethlyacetamide Prevents the High-Fat Diet-Induced Increase in Body Weight

Abstract: Increased body weight caused by visceral fat accumulation is on the rise and is reaching epidemic proportions worldwide. Hence, means and ways to tackle the problem of increased adiposity is of utmost importance. In this work, we report the effect of a water-soluble small molecule N,N-Dimethlyacetamide (DMA) on weight gain and adiposity in vitro and in vivo. To monitor the in vitro effect of DMA on adipogenesis, 3T3-L1 preadipocytes and pluripotent C2C12 cells were differentiated to adipocytes in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Ghayor et al have shown that DMA prevents osteoporosis in rats via the inhibition of osteoclast mediated bone resorption [23] and enhances bone regeneration impaired by excess in ammation [24]. In other re-purposing studies, DMA has been shown to prevent high-fat diet induced weight gain [25] and has been investigated as a potential reversible contraceptive [26]. Ghayor et al's observation that DMA acts by inhibiting NF-kB is consistent with our ndings [21][22][23].…”
Section: Introductionsupporting
confidence: 90%
“…Ghayor et al have shown that DMA prevents osteoporosis in rats via the inhibition of osteoclast mediated bone resorption [23] and enhances bone regeneration impaired by excess in ammation [24]. In other re-purposing studies, DMA has been shown to prevent high-fat diet induced weight gain [25] and has been investigated as a potential reversible contraceptive [26]. Ghayor et al's observation that DMA acts by inhibiting NF-kB is consistent with our ndings [21][22][23].…”
Section: Introductionsupporting
confidence: 90%
“…Previous studies have shown that N,N-dimethylacetamide (DMA), a common organic solvent and FDA approved drug excipient, significantly inhibits inflammatory responses in in-vivo models of preterm birth 36 , inflammatory bowel disease 37 , osteoporosis 38 and obesity 39 via inhibition of the NF-κB signaling pathway 29 . DMA is a small molecule with a molecular weight of 87 g/mol, which can easily penetrate the blood–brain barrier 40 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…These intracellular events lead to activation of the inhibitor kappa B kinase (IKK), resulting in phosphorylation of inhibitor kappa B (IκB) and its subsequent degradation by the proteasome. Degradation of IκB leads to release of NF-κB dimers (prototypically p65/p50 subunits), their translocation into the nucleus and their binding to consensus sequences of neuronal gene targets like amyloid-beta precursor protein (APP) (Pekson et Previous studies have shown that N,N-dimethylacetamide (DMA), a common organic solvent and FDA approved drug excipient, signi cantly inhibits in ammatory responses in in-vivo models of preterm birth (Sundaram et al 2013), in ammatory bowel disease (Koya et al 2022), osteoporosis (Ghayor et al 2017) and obesity (Bhattacharya et al 2019) via inhibition of the NF-κB signaling pathway (Pekson et al 2016).…”
Section: Introductionmentioning
confidence: 99%